“Meu cabelo representa a minha força”: histórias de vida de acadêmicas quilombolas da UFT - Nardes, Katiucia da Silva (2020)
In this study we present an analysis of quilombola academic narratives to understand the relation of the hair to the construction of the black woman identity, based on Gomes (2008); Munanga (1986); Mignollo (2003); Davis (2017); Gonzalez (1982) e Fanon (2008). This investigation was guided by oral and life stories of eight undergraduate black female students who are quilombola descendants from course degrees in teaching History, Geography, Pedagogy, Languages, and Chemistry in the Federal University of Tocantins. Thus, the systematization and the analysis of the life stories were done from three categories that emerged from interlocutors: family related and hair manipulation; hair transition and curly hair pride. It was concluded that the family, due to the fact they learned as a way to “protect” themselves, set beauty care patterns similar to white people. The hair transition is marked by the conciousness that what a black woman is, what enables her perception of being in the world as well as the understanding of the hair as a beauty symbol. Based on the narratives, we identify that the black people’s hair – curly hair – represents a decolonial action, whose goal is to combat the racist social practices and the eurocentrics ones. However, by analysing the narratives, we understand the meaning of hair given by the Quilombola students and their politics representation, symbolic and activist, in other words, it is not a neutral meaning in the body as a whole.